George Silvis Welsh papers - Welsh, George Silvis
Navigation book, USF Constellation (1879 November), USS Trenton (1879 December), and USS Quinnebaug (1880 September); and watch, quarter, fire, boat, battalion, station bills, etc., of the USS Trenton (1880 January).
Naval officer.
Forms part of: Naval Historical Foundation collection.
Keywords: Constellation (Frigate); Ship's papers -- 19th century; Trenton (Ship); Quinnebaug (Ship); Naval officers